Differential genetic variability at two mtDNA COI regions does not imply mismatches in Odonata molecular identification performances. Issue 1 (1st January 2021) - Maggioni, D.; Assandri, G.; Ramazzotti, F.; Magnani, D.; Pellegrino, I.; Valsecchi, E.; Galimberti, A.
Abstract: Molecular-based approaches for species identification and delimitation strongly rely, in terms of universality and efficiency, on the selected markers. Conventionally, when adopting a DNA barcoding approach to discriminate (or identify) metazoans species, the marker choice falls on the 658 base pair region at the 5ʹ end of the mitochondrial COI gene. However, a growing number of studies suggest to use alternative and more variable genetic regions, even from the same gene, such as the 3ʹ end of the COI. In this work, we compared the identification performance of the 5ʹ and 3ʹ end COI regions on a large sequence dataset of odonate species, an order of arthropods among the most studied in terms of conservation importance for aquatic ecosystems. The genetic datasets comprised a total of 236 specimens, 113 species, 51 genera and 12 families spanning the two odonate suborders Zygoptera and Anisoptera, and were analysed under an integrative multiple approach including descriptive statistics and variability of the sequences, phylogenetic reconstructions, DNA-based species delimitations, genetic distances, identification of diagnostic characters and saturation plots. All analyses were congruent in recovering the COI-3ʹ region to be slightly more variable than the COI-5ʹ one, and both regions showed a saturation of transversion at the third codon position. However, phylogenetic reconstructions, genetic distances, and diagnostic characters identification resulted in a similar discrimination power for the two COI regions. Therefore, the COI-3ʹ region does not add much information to the standard COI-5ʹ barcode region, which has in turn largely been demonstrated to successfully delineate invertebrate communities through DNA and eDNA metabarcoding, and to have a much more extensive taxonomic coverage in public databases. Overall, the DNA barcoding inventory assembled in this study will provide valuable insights into the systematics and conservation of many odonate species with implications for future DNA and eDNA monitoring-based studies.